An Investigation on Fresh and Hardened Properties of Concrete Blended with Rice Husk Ash as Cementitious Ingredient and Coal Bottom Ash as Sand Replacement Material - Bheel, N. (Springer Science and Business Media B.V., 2022)
This research offered that the rice husk ash is served as replacement for cement ingredient such as 5, 10 and 15 along with 10, 20, 30 and 40 of fine aggregates replaced with coal bottom ash in concrete. In this regard, total 180 concrete samples were prepared with mix proportion of 1:2:4 at 0.50 water/cement ratio and theses specimens were cured at 28Â days. However, the main theme of this study is to perform the slump test, compressive strength, split tensile strength and water absorption of concrete including different proportions of rice husk ash as replacement for cement and fine aggregates replaced with coal bottom ash separate and combine. The outcome was detected that the workability and water absorption is dropped as the dosages of rice husk ash and coal bottom ash increases in concrete. Moreover, the compressive and split tensile strength is enhanced by 9.10 and 7.73 while the utilizing of 5 RHA along with 30 of fine aggregate replaced with coal bottom ash in concrete at 28Â days consistently. Â© 2021, Springer Nature B.V.